2021
DOI: 10.7150/thno.55330
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 ablation inhibits glucose-stimulated insulin secretion through decreasing glycolytic flux

Abstract: Rationale: Sirtuins are NAD + -dependent protein deacylases known to have protective effects against age-related diseases such as diabetes, cancer, and neurodegenerative disease. SIRT2 is the only primarily cytoplasmic isoform and its overall role in glucose homeostasis remains uncertain. Methods: SIRT2-knockout (KO) rats were constructed to evaluate the role of SIRT2 in glucose homeostasis. The effect of SIRT2 on β-cell function was detected by investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…Nonetheless, hyperacetylation may affect the expression, structure, and function of ALDOA , which needs further exploration. Zhou et al study showed that SIRT2 inhibition promoted the protein degradation of ALDOA ( 87 ), which supported our hypothesis, although whether this regulation was caused by the hyperacetylation of ALDOA directly caused by SIRT2 inhibition is yet to be clarified.…”
Section: Discussionsupporting
confidence: 87%
“…Nonetheless, hyperacetylation may affect the expression, structure, and function of ALDOA , which needs further exploration. Zhou et al study showed that SIRT2 inhibition promoted the protein degradation of ALDOA ( 87 ), which supported our hypothesis, although whether this regulation was caused by the hyperacetylation of ALDOA directly caused by SIRT2 inhibition is yet to be clarified.…”
Section: Discussionsupporting
confidence: 87%
“…Second, we provide a mechanism showing that Cyb5r3 modulates Gck stability in β cells. Gck regulatory protein (GKRP) and B cell lymphoma-2 (BCL2)–associated agonist of cell death (BAD) modulate Gck in β cells and the liver ( 21 , 38 ). In the liver, GKRP binding stabilizes Gck, which is activated upon dissociation ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we provide a mechanism for this observation by showing that Cyb5r3 modulates Gck activity in β-cells. Gck regulatory protein (GKRP) and BAD are known to regulate Gck in β-cell and liver 22, 39 . In the liver, GKRP binding stabilizes Gck, which is activated upon dissociation 40, 41 .…”
Section: Discussionmentioning
confidence: 99%